Organized Sunday-school work in America, 1905-1908 triennial survey of Sunday-school work including the official report of the twelfth International Sunday School Convention, Louisville, Kentucky, June 18-23, 1908. - International Sunday-School Association. Executive Committee; International Sunday-School Convention of the United States and British American Provinces (12th : 1908 : Louisville, Ky.). (Chicago Executive Committee of the International Sunday-School Association, 1908)
Quadrennial, 1918- Triennial 1908-1914
"Edited ... and issued from the Office of the Association at Chicago."
Sunday-school statistics revised to date.
Keywords: Sunday-school conventions